Assembling at Ram Mandir for celebrating Dahi Handi - Mumbai Archive Project Team (Jio Institute, 2024)
Large crowds assemble at the Ram Temple to participate in the Dahi Handi event. They jostle below the pot in anticipation of the shower of dahi (curd or yogurt).